2018
DOI: 10.3390/d10030065
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution and Population Diversity of Bison in Pleistocene and Holocene Eurasia: Sex Matters

Abstract: Knowledge about the origin and evolutionary history of the bison has been improved recently owing to several genomic and paleogenomic studies published in the last two years, which elucidated large parts of the evolution of bison populations during the Upper Pleistocene and Holocene in Eurasia. The produced data, however, were interpreted in contradicting manners. Here, we have gathered, reanalyzed and compared previously published or unpublished morphometric and genetic data that have not yet been integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 62 publications
(161 reference statements)
2
28
1
Order By: Relevance
“…The data presented in these studies comprised predominantly mitochondrial D-loop data plus a handful of mitochondrial genomes (where most specimens were from either the Urals Mountains or France). These geographically and temporally limited data supported the division of ancient European bison into two distinct mitochondrial clades (wisent and CladeX in Soubrier et al (2016); or Bb2 and Bb1 in Massilani et al (2016) and Grange et al (2018)). Hereafter, we will refer to these clades according to the Bb1/Bb2 nomenclature from Massilani et al (2016) and Grange et al (2018), where 'Bb1' refers to the extinct Late Pleistocene population with a distinct mitochondrial clade and 'Bb2' refers to the living European bison (and also ancient specimens that are more closely related to living European bison than they are to Bb1).…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…The data presented in these studies comprised predominantly mitochondrial D-loop data plus a handful of mitochondrial genomes (where most specimens were from either the Urals Mountains or France). These geographically and temporally limited data supported the division of ancient European bison into two distinct mitochondrial clades (wisent and CladeX in Soubrier et al (2016); or Bb2 and Bb1 in Massilani et al (2016) and Grange et al (2018)). Hereafter, we will refer to these clades according to the Bb1/Bb2 nomenclature from Massilani et al (2016) and Grange et al (2018), where 'Bb1' refers to the extinct Late Pleistocene population with a distinct mitochondrial clade and 'Bb2' refers to the living European bison (and also ancient specimens that are more closely related to living European bison than they are to Bb1).…”
Section: Introductionsupporting
confidence: 57%
“…These geographically and temporally limited data supported the division of ancient European bison into two distinct mitochondrial clades (wisent and CladeX in Soubrier et al (2016); or Bb2 and Bb1 in Massilani et al (2016) and Grange et al (2018)). Hereafter, we will refer to these clades according to the Bb1/Bb2 nomenclature from Massilani et al (2016) and Grange et al (2018), where 'Bb1' refers to the extinct Late Pleistocene population with a distinct mitochondrial clade and 'Bb2' refers to the living European bison (and also ancient specimens that are more closely related to living European bison than they are to Bb1). It has additionally been suggested that Bb2, Bb1 and steppe bison potentially reflect distinct taxa adapted to specific ecological niches in the two regions covered by these studies (Urals mountains, Russia, and France) (Soubrier et al, 2016;Massilani et al, 2016).…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations